Factors Affecting The Incidence of Anemia in Pregnancy During The COVID-19 Pandemic - Gunawan, Lucia Sincu; Rahmawati, Juvita Tri; Puspita, Rumeyda Chitra (Jurnal Kesehatan Prima, 2024)
Anemia during pregnancy carries the risk of premature birth, low birth weight, and fetus malformations and can impose additional costs on society and families. The prevalence of anemia would be the best indicator to monitor pregnant women’s health and prevent pregnancy complications. The COVID-19 pandemic has impacted pregnant women. The prevalence of anemia in pregnancy increased from 38.33% in 2019 to 49.21% in 2020.  In the COVID-19 pandemic situation with social activity restrictions, decreasing family income, and limited access to health services, suffering from COVID-19 are risk factors for increasing the incidence of anemia in pregnancy. This study aimed to determine factors affecting the incidence of anemia in pregnancy during the COVID-19 pandemic in Karangrejo District, Magetan Regency. This study was an observational analytic study with a cross-sectional study design. The sample was selected by purposive sampling with a sample size of 52 study subjects. Data were analyzed using logistic regression analysis with SPSS. Factors that increased the incidence of anemia in pregnancy during the COVID-19 pandemic were pregnancy interval (OR=17.67; CI 95%= 1.01 to 116.00; p=0.049),  gestational age (OR=11.39; CI 95% 1.12-116.00; p= 0,040), animal protein intake  (OR= 0.25; CI 95% 0.03 – 2.38; p= 0,044), iron supplementation (OR= 108.47; CI 95% 2.36 – 4978.68; p= 0,016), consumption of tea (OR=36,89; CI95% 1.57 to 868.41; p=0.025). Mothers’ education,  family income, parity, frequency of ANC visits, and COVID-19 morbidity do not significantly affect the incidence of anemia in pregnancy. There were effects of pregnancy interval, gestational age, animal protein intake, iron supplementation, and consumption of tea on the incidence of anemia in pregnancy during the COVID-19 in Karangrejo District, Magetan Regency.  Keywords: anemia;pregnancy;COVID-19